Exploring the New Identity of Islamic Boarding School Based on Critical Challenges, Changes and Instructional Management in Post Covid-19 Pandemic - Putera, Agustian Ramadana; Wijayanti, Wiwik; Niyonsaba, Theophile (Jurnal Tarbiyatuna, 2021)
Many schools are striving to continue with normal learning due to the Covid-19 pandemic, which has greatly altered human life. Therefore, this study aimed to reveal the state of instructional management at Manbaul Ulum Islamic boarding school in Indonesia by recapping the challenges and changes teachers encounter. Descriptive methods and a qualitative approach were used to collect data from teachers working at Islamic boarding schools. Furthermore, a substantial portion of data was collected through in-depth interviews with five voluntary teachers. Based on the results, the success of instructional management should be the main focus in all the academic or religious activities at Islamic boarding schools. In addition, social, technological, and pedagogical challenges were experienced in implementing this new learning system. The sleeping arrangements in dormitories were disrupted due to the health protocols instituted to avert the adverse effects of the pandemic. Overall, different schools witnessed diverse challenges of varying magnitude.